PENGARUH KEBIJAKAN DEVIDEN TERHADAP NILAI PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGES - S Sulistyowati (MAMBA'UL 'ULUM, 2019)
The prosperity of shareholders can usually be seen from the high value of the company. This means that maximizing shareholder prosperity can be done by maximizing the value of the company. The higher the value of the company, the greater the prosperity that will be received by the shareholders. In the era of globalization, manufacturing companies in the food and beverages sector in Indonesia are trying to produce high-quality goods at low cost in order to increase competitiveness in the domestic market as well as in the global market. Most manufacturing companies in the food and beverages sector are also companies that rely on capital from investors in carrying out their production activities so it is very important for companies to maintain their liquidity health. This type of research is quantitative descriptive research with a case study method. Based on the discussion it can be concluded that dividend policy has a positive and significant effect on the value of manufacturing companies in the food and beverages sector. This is evidenced by the results of the t test value yaituthitung 3.395 and p value 0.001 < 0.05.